Glazing system with transparent insulation material for building energy saving and daylight comfort - Sun, Yanyi (2017)
Concerns over sustainability in the built environment have resulted in continuous efforts to improve the performance of window system or glazed façade and hence indoor comfort and building energy conservation. An innovative façade system where parallel transparent/translucent plastic slats are sandwiched between glass panes to form a Parallel Slat Transparent Insulation Material (PS-TIM) is proposed as a strategy to effectively reduce heat transfer between the panes of a double glazed window, while maintaining access to daylight. A holistic investigation of the window system with PS- TIMs is conducted in terms of thermal and optical properties, as well as detailed daylight and energy performance predictions of applying PS-TIMs in buildings. Firstly, an experimental investigation is undertaken in a large climate chamber, and the measurement results were used to validate a two-dimensional Computational Fluid Dynamics (CFD) model. Secondly, the validated 2D CFD model is used to solve the dynamic thermal properties of different configurations of PS-TIMs under various environmental conditions. The optical properties (i.e. Bidirectional Scattering Distribution Function (BSDF)) of PS-TIMs are obtained via a ray-tracing technique based on the structures’ geometries and the material optical characteristics of the interstitial structure. The detailed annual daylight performance in different climates and building orientations are predicted using RADIANCE. Finally, the optical and thermal properties obtained from the previous fundamental models are applied in EnergyPlus to predict the energy performance (i.e. heating, cooling and lighting energy consumption) of applying PS-TIMs in buildings in different climates. The investigation results provide a better understanding of the benefits of PS-TIM in terms of energy saving and daylight comfort improvement, as well as offer some tentative suggestions as to how architects and engineers might apply PS-TIM to window system or glazed façade.